External validation of pathological T adjustments in the ninth edition of the pleural mesothelioma tumor-node-metastasis classification - Liu, Zheng; Cai, Jingsheng; Li, Yun; Weng, Wenhan (Frontiers in Oncology, 2025)
IntroductionIn the ninth edition pleural mesothelioma (PM) pathological (p) T staging, patients with fissural invasion are upgraded from T1 to T2. This study aimed to externally validate this staging modification.MethodsResected pT1/2 PM patients were selected. The Kaplan–Meier method was applied to assess survival differences, and propensity score matching was utilized to balance baseline characteristics. Univariable and multivariable Cox analyses were conducted to determine prognostic factors. Multiple model parameters were used to evaluate the performance of the ninth and eighth edition pT staging in distinguishing between T1 and T2 patients.ResultsA total of 818 eligible patients were included, among whom 325 initially classified as T1 were reclassified as T2 due to fissural invasion, resulting in 57 patients remaining with pT1 disease. Survival analyses demonstrated that both before and after matching, the ninth edition T staging effectively differentiated between T1 and T2 patients, whereas the eighth edition did not perform as satisfactorily in distinguishing between the groups. Cox regression analyses further confirmed that the ninth edition T staging was a strong prognostic factor, whereas the eighth edition T staging was not prognostic. Lastly, model parameter results indicated that the ninth edition T staging performed better in distinguishing between T1 and T2 patients compared to the eighth edition.DiscussionOur study provided validation and endorsement for the revisions implemented in the ninth edition pT staging, specifically the reclassification of patients with fissural invasion from pT1 to pT2. This research contributed to the precise staging of PM patients.